LINQ for Visual C♯ 2008 - Ferracchiati, Fabio Claudio (FirstPress., 2008)
Every C♯ programmer needs to learn about LINQ (Language-Integrated Query), Microsoft's breakthrough technology for simplifying and unifying data access from any data source. With LINQ, you can write more elegant and flexible code-not just to access databases and files, but to manipulate data structures and XML. This book is a short, yet comprehensive guide to the major features of LINQ and the significant enhancements introduced with .NET 3.5. There is no better source for getting a head-start on the future of these technologies than this book. A clear and comprehensive yet concise introduction to using LINQ in C♯ Covers LINQ to Objects, LINQ to SQL, LINQ to DataSet, and LINQ to XML Rich in working examples of LINQ in action Ideal for C♯ programmers at any level.